2019
DOI: 10.2478/jomb-2019-0045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total LDH and its isoenzymes as markers in preeclampsia

Abstract: Summary Background Preeclampsia, a rapidly progressing pregnancy-specific multi-systemic syndrome is globally the leading cause of maternal and neonatal morbidity and mortality. This study aims to evaluate the serum total Lactate dehydrogenase levels in women with preeclampsia when compared to normotensive pregnant women and assess the electrophoretic pattern of the LDH isoenzymes in normal pregnancy, preeclampsia and eclampsia. Methods The study, carried out in the Department of Biochemistry of MVJ Medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Similarly, Khalil observed that LDH could help differentiate severe preeclampsia from healthy controls as well as patients with proteinuria, gestational hypertension and mild preeclampsia using a cut-off value of 208 U/L (sensitivity 100%, AUC 71.2%) [21]. On the other hand, Fazal et al reported that the accuracy of LDH in detecting preeclampsia was limited (sensitivity 50% at an optimal cut-off of 525 U/L) [22]; however, their sample size was particularly small to establish definitive conclusions. Kasraeian et al used a cut-off of 336 U/L and observed that the specificity was also low (59%) [23].…”
Section: Qualitative Analysismentioning
confidence: 99%
“…Similarly, Khalil observed that LDH could help differentiate severe preeclampsia from healthy controls as well as patients with proteinuria, gestational hypertension and mild preeclampsia using a cut-off value of 208 U/L (sensitivity 100%, AUC 71.2%) [21]. On the other hand, Fazal et al reported that the accuracy of LDH in detecting preeclampsia was limited (sensitivity 50% at an optimal cut-off of 525 U/L) [22]; however, their sample size was particularly small to establish definitive conclusions. Kasraeian et al used a cut-off of 336 U/L and observed that the specificity was also low (59%) [23].…”
Section: Qualitative Analysismentioning
confidence: 99%
“…This increased expression of the isoenzyme LDHA and lactate production has also been observed in the pathogenesis of other placental vascular pathologies such as pre-eclampsia [44]. Interestingly, there are multiple studies evidencing the promising use of serum LDH as a diagnostic and prognostic factor in this obstetrical condition [45,46]. Future studies may be directed to analyze serum levels of this enzyme in women with CVD and its possible clinical correlations.…”
Section: Discussionmentioning
confidence: 65%
“…Similarly, Khalil observed that LDH could help differentiate severe preeclampsia from healthy controls as well as patients with proteinuria, gestational hypertension and mild preeclampsia using a cut-off value of 208 U/L (sensitivity 100%, AUC 71.2%). 21 On the other hand, Fazal et al 22 reported that the accuracy of LDH in detecting preeclampsia was limited (sensitivity 50% at an optimal cut-off of 525 U/L); however, their sample size was particularly small to establish definitive conclusions. Kasraeian et al 23 used a cut-off of 336 U/L and observed that the specificity was also low (59%).…”
Section: Qualitativeanalysismentioning
confidence: 99%